2000
DOI: 10.1021/la9913351
|View full text |Cite
|
Sign up to set email alerts
|

Average Orientation and Location of Benzyl Alcohol-d5 and Alkyl Benzyl-d5 Ethers in Anionic Nematic Lyotropic Liquid Crystals

Abstract: Deuterium quadrupole splittings of benzyl alcohol-d 5 and a series of alkyl benzyl-d 5 ethers, with linear aliphatic chains from 1 to 12 carbon atoms, were measured using 2H NMR spectroscopy. These molecules were dissolved in ND anionic nematic lyotropic liquid crystals prepared with sodium decyl sulfate (NaDS) and cesium decyl sulfate (CsDS). Using the quadrupole splittings, the two order parameters that completely describe the average orientation of the aromatic ring were calculated. From these values, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Their results indicate that benzyl alcohol is located at the interface, close to the carbonyl group of the phospholipids, oriented with the methylene group toward the hydrophobic region of the bilayer. Later, we measured the quadrupole splittings and estimated the order parameters of the aromatic ring of the series C 0 −C 12 , dissolved in anionic nematic lyotropic liquid crystals . The results suggested that C 0 was also located at the bilayer interface, but with a different orientation of the ring relative to the previous observation in vesicles .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Their results indicate that benzyl alcohol is located at the interface, close to the carbonyl group of the phospholipids, oriented with the methylene group toward the hydrophobic region of the bilayer. Later, we measured the quadrupole splittings and estimated the order parameters of the aromatic ring of the series C 0 −C 12 , dissolved in anionic nematic lyotropic liquid crystals . The results suggested that C 0 was also located at the bilayer interface, but with a different orientation of the ring relative to the previous observation in vesicles .…”
Section: Discussionmentioning
confidence: 76%
“…A deeper understanding of these processes is of fundamental importance in drug activity and design. A broad range of experimental and theoretical methodologies, such as 2 H NMR quadrupole splitting, relaxation time measurements, and molecular dynamics (MD) simulations, among others, have been used to study different aspects of these assemblies. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between biologically interesting molecules and molecular assemblies, such as micelles, vesicles, bilayers, liposomes, and liquid crystals, are a subject of current research interest. The molecular composition of living matter is essentially chiral, and specific interactions between chiral molecules are known to be crucial in most biological processes. With this in mind it seems reasonable that specific interactions between chiral centers might influence the distribution as well as diffusion of chiral biologically active molecules across natural membranes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the simplest methods to estimate the average alignment of ions and molecules in anisotropic media, such as an oriented bilayer, is by using order parameters derived from the 2 H NMR spectra of specifically labeled molecules. In the past, we have studied the solubilization process of a number of ions and molecules in cationic and anionic nematic lyotropic liquid crystals, using deuterium quadrupole splittings of deuterated aromatic rings. , In this work, we have employed 2 H NMR spectroscopy to measure the deuterium quadrupole splittings from the fully deuterated aromatic ring of two series of seven optical isomers each, l - and d - N -acyl-1-phenyl-2-aminopropane, 40% d 5 . Both series contain linear acyl substituents ranging from 1 to 10 carbon atoms and were dissolved in a nematic cholesteric lyomesophase prepared using cesium N -dodecanoyl- l -alaninate (CsD- l -Ala) as the main surfactant component, providing the chiral interface.…”
Section: Introductionmentioning
confidence: 99%